The Role of Multimedia Technology in Enhancing Distance Learning - Afkar, Muhammad Agha (Lembaga KITA, 2024)
This study aims to analyze the role of multimedia technology in enhancing the effectiveness of distance learning in Banda Aceh. Multimedia technology, including videos, animations, simulations, and various online learning platforms, is believed to significantly enrich the teaching and learning process in remote educational environments. The research employs a descriptive quantitative method, utilizing surveys to collect data from students and teachers involved in distance learning across Banda Aceh. The study's population comprises students and teachers from schools that have adopted distance learning, with a randomly selected sample to ensure a representative distribution across different educational levels and socio-economic backgrounds. Data were gathered through questionnaires and interviews, and subsequently analyzed using descriptive statistics. The findings reveal that multimedia technology plays a crucial role in enhancing the effectiveness of distance learning. Among the various technologies, interactive videos and animations were identified as the most effective by both students and teachers. Additionally, the study found that the integration of multimedia technology received positive feedback, with respondents noting that it made learning more engaging and easier to comprehend. This research underscores the importance of incorporating multimedia technology in distance learning to improve educational quality in Banda Aceh. The study also provides recommendations for further teacher training and the development of more advanced multimedia-based educational tools. These findings are expected to contribute positively to educational policy development in Banda Aceh and serve as a reference for educators and educational technology developers